Efeitos da vincristina e do guaraná em cultura celular de cérebro e cerebelo de camundongos na viabilidade celular e metabolismo oxidativo - Veloso, Carolina Fantinel (2014)
Vincristine is a chemotherapeutic agent used to treat various types of cancers with effective clinical outcomes. However, its effects include a number of disorders related to balance, such as ataxia, tremors and peripheral neuropathy. These damages are likely associated with poisoning by the drug in the central and peripheral nervous systems. There is evidence that guarana (Paullinia cupana) may have neuroprotective effects on the central nervous system. The aim of this study was to evaluate the effects of vincristine and guarana on cell viability and oxidative metabolism in vitro cell cultures of mice brain and cerebellum. The cells were incubated for 24 and 72 hours in a specific medium (DMEM) and treated with vincristine at a concentration 0.009 mM for 24 hours and 0.0007 mM for 72 hours and at concentrations of 10, 30, 100 and 300μg/m Lof guarana extract. Incubation was followed by MTT and Pico Green ® tests and evaluation of catalase, superoxide dismutase and thiol activity (cell viability), as well as TBARS, protein carbonyls and dichlorodihydrofluorescein (oxidative metabolism). The results indicated that vincristine may cause cytotoxic effects in mice cerebellum and brain and that guarana may reverse this cytotoxicity in concentrations 100 e 300μg/mL.